Mobilidade e acessibilidade ao transporte coletivo por ônibus: evidências e contradições no caso de Belo Horizonte-MG - Daniela Antunes Lessa (2019)
Cities are composed of constructed spaces and networks, whose main function is to support economic, social, cultural and environmental processes. Space is history and, from this perspective, a city is the result of a process of transformation: a 'palimpsest' of overlapping past forms and a 'collage' of current uses, many of which can be ephemeral. The infrastructure and the possibility of displacement of goods, people and information, translated into the concepts of accessibility and mobility, are aspects/elements of the process of (re)production of urban space. In this thesis, the concept of mobility does not only refer to the best displacement from one point to another (circulation), or to the existence of road infrastructure and various modes of transport (accessibility). It incorporates the notion of circulation, which allows expanding the possibilities of appropriation and collective and individual use of urban space. On the other hand, the concept of accessibility, more than the strictu sensu movement itself, is related to the ability to reach desired destinations, with the combination of locations and characteristics of the transport system, considering the geographic distribution of the population and economic activities, as well as the corresponding characteristics. As in other Brazilian capitals, Belo Horizonte shows the proliferation of a series of precarious situations in the supply of accessibility and urban mobility, a reflection of the historical (in)capacity of intervention by public authorities in the face of the excluding urbanization processes and the vicious circles that permeate the processes of social inclusion and socioeconomic development. Unlike the classic formats, this thesis follows an alternative format based on a sequence of three scientific articles, whose main objective is the analysis of the current conditions of mobility and accessibility to bus transportation, as well as its supposed influence on the process of formation/consolidation of new centralities and breaking away from the classic center-periphery model. In the opposite direction, it is intended to evaluate whether this "fractal" organizational logic of contemporary cities has allowed the rearrangement of bus transportation flows in these subcentres and immediate surroundings, in order to avoid large displacements to the Central Area of the municipality, as recommended by the Master Plan of Belo Horizonte. The results showed significant regional differences in the level of accessibility to bus transport in the municipality of Belo Horizonte. There are even spaces that are characterized as a public priority for intervention, where low levels of accessibility are accompanied by high demand for mobility. Also, unlike studies that suggest a strong process of decentralization and disruption of the traditional center-periphery model, the results presented indicate that the spatial structure of Belo Horizonte has remained highly concentrated in the Central Area, although some urban centralities have stood out and in a not yet extensive way, produce changes in the distribution of bus flows.